2018
DOI: 10.1111/raq.12282
|View full text |Cite
|
Sign up to set email alerts
|

The importance of behaviour in improving the production of shrimp in aquaculture

Abstract: There is an increasing recognition within the aquaculture industry that understanding the behaviour of farmed animals can help provide solutions to feeding problems. However, most studies have focused on finfish production, with fewer behavioural studies on feeding processes in commercially produced crustaceans. More than 60% of crustacean aquaculture is attributed to the production of penaeids, particularly the Pacific white-leg shrimp (Litopenaeus vannamei Boone). The profitability of the Pacific white-leg s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 285 publications
(499 reference statements)
0
40
1
1
Order By: Relevance
“…Many countries in the Americas and Asia rely on the production of such shrimp and thus, it is the fastest-growing crustacean aquaculture sector. Whiteleg shrimp (Litopenaeus vannamei) is the most widely reared shrimp species due to its hardiness to diseases, high stocking densities, tolerance to a wide range of water quality parameters (salinity, temperature, NO3 -), and improved growth performance compared to the tiger shrimp (Penaeus monodon Fabricius) (Bardera et al, 2019). A previous study by Otoshi, Arce, and Moss (2003) showed comparable production capacities of broodstock shrimp (Litopenaeus vannamei) reared in both RAS and flow-through earthen ponds.…”
Section: Penaeids and Ostreidsmentioning
confidence: 99%
“…Many countries in the Americas and Asia rely on the production of such shrimp and thus, it is the fastest-growing crustacean aquaculture sector. Whiteleg shrimp (Litopenaeus vannamei) is the most widely reared shrimp species due to its hardiness to diseases, high stocking densities, tolerance to a wide range of water quality parameters (salinity, temperature, NO3 -), and improved growth performance compared to the tiger shrimp (Penaeus monodon Fabricius) (Bardera et al, 2019). A previous study by Otoshi, Arce, and Moss (2003) showed comparable production capacities of broodstock shrimp (Litopenaeus vannamei) reared in both RAS and flow-through earthen ponds.…”
Section: Penaeids and Ostreidsmentioning
confidence: 99%
“…However, despite this production volume, shrimp farming is prone to significant inefficiencies with regards to feeding, which can comprise up to half of total production costs (Silva et al 2012;Engle et al 2017). Shrimp can be slow to feed on pellets (Gadient & Schai 1994), and feeding behaviour can vary greatly depending on shrimp physiological condition and environmental factors (Bardera et al 2018). This often results in feed losses for farmers leading to increases in the feed conversion ratio (FCR), degradation of chemical and microbiological water quality, higher nutrient discharge rates into the environment (Smith et al 2002;Li et al 2017;Jescovitch et al 2018;Ullman et al 2019a) and increases in water exchange requirements (Davis et al 2006).…”
Section: Overview Of Shrimp Feeding Behaviourmentioning
confidence: 99%
“…Feeding is the primary factor for determining the efficiency and cost of aqua feed, which may represent a considerable proportion of the crustacean farming budget [ 23 ]. Crustaceans use visual, mechanoreceptor, and chemoreceptor systems to detect the location of food sources, and when food is available, crustaceans change their sound signatures and movements [ 24 ].…”
Section: Important Behaviors In Crustacean Aquaculturementioning
confidence: 99%